Inovasi Pelayanan Publik Dalam Penerapan e-Government di Polresta Palu: Studi Kasus Aplikasi Sinar (SIM Nasional Presisi) - Putri, Rahmadea Sagita; Nasrullah; Royfandi, Mohammad (JPS: Journal of Publicness Studies, 2025)
This research aims to identify the public service innovation in the implementation of e-government at Polresta Palu through the SINAR (SIM Nasional Presisi) application, using the "Diffusion of Innovations" theory proposed by Everett Rogers (2003), which consists of five aspects: Relative Advantage, Compatibility, Complexity, Trialability, and Observability. The foundation of this research is qualitative with a descriptive research type and qualitative approach. Data collection techniques used include observation, interviews, and documentation, with six informants. The results of this study indicate that the SINAR application is a relatively good innovation in public services and egovernment implementation at Polresta Palu. However, the application is not yet fully effective because only the SIM renewal feature can be used, while other features are still not functional. The application still requires several improvements to overcome existing obstacles and enhance publicity to increase the adoption of SINAR among the community. In terms of Complexity, some data confuse the public, and there are network issues. The Observability aspect also needs improvement, as the author observes a lack of effective publicity, resulting in many people being unaware of and not using this application. Several suggestions from SINAR users also need to be considered to improve service quality.